Relationship Between of Protein Level Intake and Perineal Wound Healing - Indrianingrattu, Nindi; Fatmaningrum, Widati; Setyowati, Dewi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: The perineum is at risk of injury either spontaneously or by episiotomy during labor. Perineal wounds usually heal within 6-7 days postpartum. Healing of perineal wounds can be influenced by protein consumption in postpartum mothers. This purpose of this study was to determine the relationship between the levels of protein consumption with the perineal wound healing in postpartum mothers.Subjects and Method: This cross sectional study conducted at Ciawi Public Health Center, West Java, in September-November 2022. The sample in this study were postpartum mothers who gave birth normally with perineal wounds at Ciawi Public Health Center. Sample selection used a purposive sampling method and the sample size was 67 respondents. The dependent variable was perineal wound healing. The independent variable was the level of protein consumption. The research instrument used a REEDA Scale observation sheet and Food Recall 24 hours questionaire. Data were analyzed using Chi-square test.Results: Healing of perineal wounds in postpartum mothers was good for 65 respondents (97%), postpartum mothers who had sufficient levels protein consumption levels were 33 respondents (49,3%). The results show that there is no relationship between perineal wound healing and the level of protein consumption (p= 0.197).Conclusion: There is no relationship between the level of protein consumption with the perineal wound healing